The Impact of the COVID-19 Pandemic on the Tourism Sector in Jawa Tengah Province - Karnowahadi; Endang Sulistiyani; Dody Setyadi (Entrepreneurship and Small Business Research, 2022)
The COVID-19 pandemic has resulted in economic paralysis in various countries around the world. One of the provinces in Indonesia, namely Jawa Tengah Province which is a mainstay of world tourist destinations, cannot be separated from the impact of COVID-19. The tourism sector in Jawa Tengah Province contributes less than 10% of the Gross Regional Domestic Product. The COVID-19 pandemic has resulted in a decrease in the contribution of the tourism sector to Jawa Tengah's Gross Regional Domestic Product by more than 50%. The number of tourists who fell during the pandemic resulted in decreased tourism sector income. Although the average length of stay did not decrease, hotel occupancy rates continued to decline during the pandemic. The social impacts caused by COVID-19 include people preferring to stay at home instead of talking to their neighbors, people don't like crowds, community groups are more protective of their environment (by making environmental entrance gates). The Jawa Tengah Provincial Government with the permission of the Central Government took a policy of regeneration of the tourism sector without neglecting the protection of public health.